16. THE RELATIONSHIP BETWEEN DIABETES KNOWLEDGE AND GLYCEMIC CONTROL AMONG PATIENTS WITH DIABETES TYPE 2 AT HUE UNIVERSITY OF MEDICINE AND PHARMACY HOSPITAL, 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To assess glycemic control and diabetes-related knowledge among patients with type 2 diabetes mellitus, and to explore factors associated with glycemic control.Methods: A cross-sectional study was conducted on 150 patients, conveniently sampled between October 2024 and April 2025. Diabetes Knowledge Questionnaire (DKQ-24) was used to evaluate patients' disease knowledge. Logistic regression analysis was performed to identify factors associated with HbA1c control.Results: A total of 60.7% of patients achieved good glycemic control (HbA1C < 7%), with a mean knowledge score of 11.64 ± 2.27. Better diabetes knowledge was associated with improved glycemic control.Conclusion: The proportion of patients achieving good HbA1c control was relatively favorable, reflecting positive treatment outcomes at the study site. Good disease knowledge served as a protective factor contributing to better glycemic management, alongside other factors such as residential area and comorbidities. Strengthening health education programs and individualized management support at the community level is essential to further improve treatment outcomes.
Keywords: Type 2 diabetes mellitus; HbA1C; glycemic control; disease knowledge; DKQ-24.